2000
DOI: 10.1111/j.1540-8159.2000.tb07063.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Value of Baroreflex Sensitivity Determined by Spectral Analysis in Risk Stratification After Myocardial Infarction

Abstract: The risk of cardiac death in patients after MI is predicted by a decreased baroreflex sensitivity (BRS). The critical value of BRS based on phenylephrine administration is 3 ms/mmHg. The aim of this study was to determine the critical value of BRS assessed by spectral analysis of spontaneous fluctuations in pulse intervals and blood pressure. Digital blood pressure was recorded noninvasively (3 min, controlled breathing 0.33 Hz) in 112 patients, 8–18 days after MI. Nine patients died during the first year afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…In this study, IBI intervals were assessed from the finger blood pressure signal. We have used the IBI signal for BRS determination since 1992 (Honzikova et al 1992) with comparable results based on the measurement of R-R intervals from ECG (Persson et al 2001, Honzikova et al 2000b. However, R-R intervals are normally used.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, IBI intervals were assessed from the finger blood pressure signal. We have used the IBI signal for BRS determination since 1992 (Honzikova et al 1992) with comparable results based on the measurement of R-R intervals from ECG (Persson et al 2001, Honzikova et al 2000b. However, R-R intervals are normally used.…”
Section: Discussionmentioning
confidence: 99%
“…High-frequency paced breathing (0.25 or 0.33 Hz) is required to avoid overestimation when measuring BRS LF [10,11]. This is because spontaneous breathing in humans is spread over a wide range of frequencies [12] and breathing in the 0.1 Hz range will cause a greater BRS LF value due to respiration-related nonbaroreflex-mediated R-R interval fluctuations in the low-frequency band [13].…”
Section: Introductionmentioning
confidence: 97%
“…Reduced BEI and BRSseq predict all-cause mortality and sudden death, respectively, in hypertensive patients with chronic renal failure [9]. Furthermore, a BRS LF less than 3 ms/mmHg is significantly associated with cardiac events in heart failure patients [10] and is able to predict cardiac death in patients after myocardial infarction [11].…”
Section: Introductionmentioning
confidence: 99%
“…2-5 BRS lower than 3 ms/mm Hg is a powerful independent prognostic risk factor for sudden cardiac death. 32,33 An enhanced BRS had beneficial effects on the outcome of patients with cardiovascular disease, possibly by preventing ventricular arrhythmias. 34 Chao et al found that patients with carotid artery stenosis exhibited a significant reduction in BRS compared with controls.…”
Section: Discussionmentioning
confidence: 99%